Penerapan Metode Ummi Dalam Meningkatkan Kualitas Bacaan Al-Qur’an Di UPT SDN 56 Salodua Enrekang - Hasanuddin, Nasri; Mustamin, Mustamin; Ahmad, Ahmad; Tahir, Ilyas; Sudarmono, Muh Aidil (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study examines how the Ummi technique can be used to help fifth grade students at UPT SDN 56 Salodua, Enrekang Regency, read the Qur'an more fluently. The focus of this study was Islamic Religious Education Teachers and fifth grade students at UPT SDN 56 Salodua, Enrekang Regency, with a total of 27 students, including 13 males and 14 females. Classroom action research (CAR) was conducted in two cycles, each of which included planning, action, observation, and reflection. Because some students did not achieve the KKM in the first cycle, a second cycle was conducted. The results of the study showed that the use of the Ummi method significantly improved the quality of students' reading of the Qur'an. As many as 92% of students completed it in cycle II, up from 63% in cycle I. These results indicate how well the Ummi technique works to help fifth grade students at UPT SDN 56 Salodua become more proficient readers of the Qur'an.